Experimental Approaches for Testing if Tolerance Curves Are Useful for Predicting Fitness in Fluctuating Environments - Ketola, Tarmo; Kristensen, Torsten N. (Frontiers in Ecology and Evolution, 2017)
Most experimental studies on adaptation to stressful environments are performed under conditions that are typically rather constant and rarely ecologically relevant. Fluctuations in natural environmental conditions are ubiquitous and include for example variation in intensity and duration of temperature, droughts, parasite loads, and availability of nutrients, predators and competitors. The frequency and amplitude of many of these fluctuations are expected to increase with climate change. Tolerance curves are often used to describe fitness components across environmental gradients. Such curves can be obtained by assessing performance in a range of constant environmental conditions. In this perspective we shortly list theoretical and experimental evidence why results obtained under constant environmental conditions might be misleading for processes in nature and therefore may not be suitable for predicting fitness and future species distribution and abundance. We further suggest experimental avenues that can provide a better foundation for forecasts of the distribution of biota.